Food stainless steel. Characteristics. Spheres of application - B. M. Nemenenok; A. R. Tsyganov; A. S. Panasyugin; I. A. Pankovets; N. P. Masherova; N. D. Pavlovsky (Литьë и металлургия)
Specificity of food preparation provides a number of repeated sanitary and hygienic measures with the use of hot water, washing and disinfecting solutions of different pH, concentration, temperature and time of exposure, which can provoke the beginning of corrosion process on poor‑quality equipment, both on the external and internal surfaces of the equipment. The thermal operating temperature of cookware ranges from –15 °C (refrigerator) to +100 °C (up to +250 °C when used in an oven). All the above‑mentioned steel grades fully meet the corrosion resistance requirements for cookware. Tanks made of these steels cannot be subject to corrosion under any normal operating conditions specified by the manufacturer. The main criterion for the suitability of a particular stainless steel for food applications is its chemical inertness and the permissible amounts of migration of the chemical elements that make up the steel from the products into the modelling medium.